Nursing experience of a case of mannitol extravasation treated by medical cold dressing wet compress combined with Ruyi Jinhuang powder external application (医用冷敷敷料湿敷联合如意金黄散外敷治疗甘露醇外渗1例的护理体会) - ZHANG Pin (张聘); LIU Jie (刘洁) (中西医结合护理)
This paper summarized the nursing experience of a case of local swelling of the back of the hand caused by drug extravasation after infusion of 20% mannitol through peripheral venous indwelling catheter. Medical cold dressing wet compress and Ruyi Jinhuang powder external application were applied alternately once a day, and the measured value of hand circumference and pain score were recorded. After three days of treatment, the measured value of hand circumference and pain score decreased, and the skin elasticity recovered well. Medical cold dressing wet compress combined with Ruyi Jinhuang powder external application is effective and easy-to-use in treatment of adverse reactions caused by 20% mannitol drug extravasation. (本文总结1例经外周静脉留置针输注20%甘露醇后药物外渗导致手背局部肿胀的患者的护理体会。采用医用冷敷敷料湿敷与如意金黄散交替外敷, 1次/d, 治疗期间记录手围测量数值及疼痛评分。经3天治疗, 患者手围测量数值及疼痛评分均降低, 皮肤弹性恢复良好。甘露醇药物外渗后, 采用医用冷敷敷料湿敷联合如意金黄散外敷治疗方法, 见效快、操作简单、效果良好。)